Perempuan dan Teror: Memahami Peran Kombatan Perempuan dalam Kampanye ISIS - Nida Fajrin Nafisah (Universitas Airlangga, 2021)
At this time, writing about women in the Islamic State of Iraq and Syria campaign has focused on their role as supporters. While in acts of terror, ISIS often turns women into combatans in ISIS terror acts. The study was conducted with a content analysis method for documents discussing the acrion of ISIS in Iraq, Syria and Southeast Asia and analyzed by transnational crime theory. Since the development of globalization and the advancement of information, technology communication, terrorist groups have been easier to create transnational terrorism networks because they are supported by various technological conveniences. ISIS makes use of these modern tools to spread their ideology, find and recruit new members from all corners of the world more easily. In recent years ISIS suffered a major defeat that changed the map and strategy of terror. This article concludes that women have been incarnated as subjects in ISIS international terrorism. The use of women as combatants in ISIS terror attacks is unusual. Thoughts that ISIS has implanted since 2015 produced various results by doing new terror attacks with women as perpetrators. Deradicalization then carried out by military and non-military ways. The military way to attack ISIS actions with military weapons, while the non-military way by changing the thoughts of the perpetrators.